Diurnal Activity Patterns and Feeding Behavior of Sloth Bear (Melursus Ursinus) during Wet and Dry Seasons in Wilpattu National Park, Sri Lanka - Weerasekera, Danushka S; Madhushanka, Shashi; Jayaweera, Malmi; Ranwana, Kithsiri B (GEOGRAFI, 2025)
This study examines the seasonal behavioral patterns of sloth bears (Melursus ursinus) in Wilpattu National Park, Sri Lanka, focusing on their activities and feeding behaviors during the dry and wet seasons. Systematic field observations were conducted to record the frequency of six key behaviors: Walking, Bedding down, Self-grooming, Fighting or Chasing, Defecation and Urination, and Hydration. Chi-squared tests were used to assess seasonal differences, revealing significant variations in Walking (χ² = 32.895, p < 0.001), Bedding down (χ² = 4.5, p = 0.034), and Fighting or Chasing (χ² = 5.444, p = 0.020). These behaviors were influenced by seasonal factors such as food and water availability, temperature, and shelter conditions. In contrast, Self-grooming, Defecation and Urination, and Hydration showed no significant seasonal differences (p > 0.05). Activity patterns indicated increased activity in the morning and afternoon, with reduced activity in the evening. Feeding duration did not differ significantly between seasons (W = 81, p = 0.535), though the distribution of feed types varied, with ants and termites being more prevalent in the wet season and berries in the dry season. These findings suggest that sloth bears adjust their behavior and feeding strategies to seasonal changes in resource availability. Understanding these patterns is essential for effective conservation and management of sloth bear populations.